Telaah akar hyperinflasi: Kajian terhadap krisis moneter di Indonesia pada tahun 1997-1998 - Alamsyah, Risky; Aditya, Muhammad Rifqi (Maliki Interdisciplinary Journal, 2024)
This research is oriented to examine the roots of hyperinflation that occurred during the monetary crisis in Indonesia in 1997-1998. This research uses a literature review type of research conducted by reviewing all references in the form of articles, journals, and books that are in line with the research title. The data collection method used in this research is secondary data obtained from journals, articles, books, documentation, web, brochures, and electronic media that are aligned with the research objectives. The results of this study state that the roots of hyperinflation that occurred in Indonesia in 1997-1998 include; (1) Weakening of the Rupiah Exchange Rate against the US Dollar (2) High Foreign Debt (3) Failed International Monetary Fund (IMF) Policies (4) Government Inability to Overcome the Crisis.